Efeito da ingestão do suco de beterraba na resposta hipotensora e estresse oxidativo após uma sessão de exercício aeróbio em indivíduos com hipertensão arterial - Muniz, Mygeive Sheldon Ferreira (2023)
Research shows that the nitrate present in vegetables such as beets, has vasodilator effects and promotes blood pressure reduction. Similar to the nutrient, exercise acts as an effective approach to the promotion of post exercise hypotension (HPE), however , the acute effect of beet root juice on blood pressure and oxidative stress in hypertensive people is still little known. The aim of the study is to evaluate its acute effect on HPE of these individuals. Randomized, controlled and cross tracked single arm crossover clinical trial conducted with 13 hypertensive patients from 30 to 60 years of age who performed three conditions in which they were supplemented with 500 ml of beet juice with exercise (BET+EX), 200 ml of mixed drink with activity (BM+EX) and 250 ml of water before non exercise control (CON). Two hours later, they performed a 40 minute aerobic exercise on a treadmill . Clinical blood pressure (PA) was measured before and during 60 minute recovery every 10 minutes after exercise or rest. Plasma nitr ite, total antioxidant capacity and malondialdehyde were analysed. ANOVA two way for repeated measurements was adopted to compare differences in systolic, diastolic HPE, heart rate and subjective perception of stress. Statistical analysis showed significan t differences in plasma nitrite between beet juice and mixed drink (BM+EX:42.6 ± 8.8 μ M vs. BET+EX: 59,9 ± 9,1 μ M, p=0,037) throughout the intervention, however there were no changes to total antioxidant capacity (CAOT) and malondialdehyde (MDA). BET+EX pr omoted systolic HPE (PAS: 132.7 ± 11.7 to 121 ± 19.1 mmHg at 60 minutes after exercise, p<0,001), but did not promote diastolic HPEs (PAD: 87.7± 13.9 to 82.5 ± 13.2 mm Hg, p=0.074). BM+EX promoted systolic hypotensive response (PAS:129,4±12,6 to 123,1±12,8 mmHg, 60 minutes post exercise, p<0,001), without diastolic HPE (PAD: 88,2±7,4 to 85,5±9,8 mm Hg, p=0,074). CON did not promote either systolic HPE (PAS: 127.3±16.9 to 124.5±17.1 mmHg, at 60 minutes during rest p<0,001), or diastolic (PAD: 86.6±8.4 to 84. 6±9.1 mm Hg, p=0.074). Significant differences were observed in the time interaction for systolic hypotensive response in the first 30 minutes (BET+EX: 12.3±2.8; BM+Ex: 11.3±2,6; CON: 0.4±2.3 mmHg, p=0.041) and 40 minutes post exercise (BET+EX: 18.1±2. 9; CON: 2,4±3.1 mmH g, p =0.012). No differences were perceived between BET+EX and BM+EX (p=1,0). The magnitude of diastolic HPE was not different between procedures (p=0.217). There was a significant reduction in systolic blood pressure after a single exercise session, unlike diastolic. The hypotensive response was not ercise session, unlike diastolic. The hypotensive response was not improved and oxidative stress was not increased as a result of beetimproved and oxidative stress was not increased as a result of beetrootroot juice.juice.